Peyton's near-death phantasy in ambrose bierce's an occurrence at owl creek bridge - Suhaelatul Faizah Ahmad (Faculty of Adab and Cultural Sciences State Islamic University Sunan Kalijaga, 2015)
st,1/ws.c.1